Comparison of pain scale preferences and pain intensity according to pain scales among Turkish Patients: a descriptive study. - Yazici Sayin, Yazile; Akyolcu, Neriman (My University, 2014)
Pain scale preferences may vary among patients. Providing a choice of which pain scale to use might be helpful for patients. The aim of this study was to determine patient pain scale preferences and compare the level of agreement among pain scales commonly used during postoperative pain assessment. A total of 621 patients during the early postoperative period were enrolled in this descriptive study. A questionnaire form, the faces pain scale (FPS), visual analog scale (VAS), numeric rating scale (NRS), verbal descriptor scale (VDS), thermometer pain scale (TPS), McGill Pain Questionnaire (MPQ), Short-form McGill Pain Questionnaire (SFMPQ), and Brief Pain Inventory (BPI) were used to collect data. Most patients reported that their pain was not measured with any of the pain scales. Patient preference for pain scales were as follows: 97.4% FPS, 88.6% NRS, 84.1% VDS, 78.1% TPS, 60.1% SFMPQ, 37.0% BPI, 11.4% VAS, and 10.5% MPQ. Education was an important factor in the preferences for all scales (p < .000). The level of pain determined by the VAS did not correlate with the level of pain identified by the NRS, TPS, FPS, and VDS (p < .05). There was no difference among the levels of pain for the NRS, TPS, FPS and VDS (p > .05), but there was for the VAS (p < .05). The pain scales chosen should be reliable, valid, and able to evaluate the effects of treatment. The results suggest that the NRS, TPS, FPS, and VDS were appropriate pain rating scales for the participants in this study, and that the VAS should be used in combination with one of these scales.